Analisis Kadmium (CD), Seng (ZN) Dan Timbal (PB) Pada Susu Kental Manis Kemasan Kaleng Secara Spektrofotometri Serapan Atom (SSA) - Roslinda Rasyid; Humairah Humairah; Zulharmitta Zulharmitta (Jurnal Farmasi Higea, 2013)
The quantitation of same metal such as cadmium, zink and lead from same sweetened condensed milk packed in the cans samples wich are collected in Pasar Raya Padang has been done. Metal measurament done by Atomic Aborbtion Spectroscopy (AAS). The result showed it’s zink quantity from sample A, B, C dan D are 24.3948 mg/Kg; 23.7886mg/Kg; 19.3428 mg/Kg; 19.3928 mg/Kg respectily, it’s cadmium were not identified, It’s lead quantity are 0.1434 mg/Kg; 0 mg/Kg; 0 mg/Kg; 0.1436 mg/Kg. It showed that sample A, and D have not complied the milk qualification of BPOM. RI. No. 03725/B/SK/VII/89 in metal compound.